Inexistence of permafrost at the top of the Veleta peak (Sierra Nevada, Spain) - Oliva, Marc (2017)
A 114.5m deep drilling was carried out in August 2000 in the bedrock of the Veleta peak, at 3380m in the massif of Sierra Nevada, Southern Spain. The objective of this work is to analyse temperatures at the first 60m depth of this drilling from September 2002 to August 2013 based on 11 UTL-1 thermal loggers located at different depths, together with air temperatures at the summit of the Veleta peak. Permanent negative temperatures have not been detected in the borehole, which shows evidence of the absence of widespread permafrost conditions nowadays in the highest lands of this massif. Bedrock temperatures oscillated between 3.2°C at 0.6m depth and 2°C at 20m below the surface. The largest temperature ranges were recorded on the most external sensors until 1.2m depth, where values reached 22.3°C. Seasonal temperature variations were significant until 10m depth. The thickness of the seasonal frozen layer was highly variable (0.6-2m) and dependent on annual climate conditions. The mean air temperature at the Veleta peak increased by 0.12°C during the study period. Bedrock temperatures followed diverging trends: a drop of 0.3-0.4°C down to 0.6m depth, a decrease of up to 0.7°C between 4 and 10m, thermal stability at 20m and a rise of 0.2°C that occurred in 2009 at the deepest sensor at 60m. The calculation of the thermal wave damping in the subsoil of the Veleta peak has allowed for quantifying the thermal diffusivity of the rock as (7.05±0.03)10(-7)m(2)/s, which means that the external climate signal arrives with an 8.5-year lag to the sensor at 60m deep. This allows to deduce a trend change in the climate of the area, moving from warmer conditions towards a trend of cooling from 2006 to 2007.